Operating Experience and Analysis of Engine Operated on Ethanol - Diesel Emulsion (Global Journals of Research in Engineering, 2011)
Ethanol is a bio-based renewable and oxygenated fuel, thereby providing potential to reduce the PM emission in diesel engines and to provide reduction in life cycle CO2. Although ethanol has been used as fuels oxygenate to reduce tail-pipe emissions in gasoline, its use in diesel has been limited due to technical limitations (i.e., blending). Commercially viable e-diesel is now possible due to the development of a new additive system. Tetra Methyl Ammonium Bromide, a new additive allows the splash blending of ethanol in diesel. The objective of this investigation is to first create a stable ethanol-diesel emulsified fuel with 2% Tetra Methyl Ammonium Bromide additive, and then to generate transient performance, combustion and emissions data for evaluation of different ethanol content on a diesel engine. A singlecylinder, air-cooled, direct injection diesel engine developing a power output of 5.2 kW at 1500 rev/min was used. Base data was generated with standard diesel fuel. Subsequently three fuel blends, namely 80D: 20E, 75D: 25E, 70D: 30E and 65D: 35E by volume were prepared and tested. Engine performance and emission data were used to optimize the blends for reducing emission and improving performance. Results show almost equal performance for 90D: 10E blends with reduced emissions compared to neat fuel.
Keywords: Oxygenated fuel; additive; alternate fuels; performance and emission